The Importance of Work Stress and K3 (Occupational Health and Safety) in Assessing Employee Performance - Nihayati, Indah; Bahri, Moh. Saiful; Pujiastuti, Agustina; Yatiningrum, Agung (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
It is very important to pay attention to factors that can affect employee performance, such as work stress experienced by employees or occupational safety and health. This research was conducted at PT. Akas Mila Sejahtera Probolinggo with the objectives (1) To determine the simultaneous effect of work stress and K3 (Occupational Health and Safety) on employee performance. (2) To determine the partial effect of work stress and K3 (Occupational Health and Safety) on employee performance. (3) To determine the dominant influence between work stress and K3 (Occupational Health and Safety) on employee performance. The population of this research is the employees of PT. Akas Mila Sejahtera City of Probolinggo, amounting to 90 people. The sample taken by the Slovin method is as many as 73 people, with the criteria of employees who work as drivers, kondiktur, kernet and workshops with incidental data collection techniques. The approach used is quantitative with analysis using SPSS software. The results showed that work stress and K3 (Occupational Health and Safety) had a significant effect on employee performance.